Analysis of the heavy metal contents’ effect on steroidal saponins and the anti-breast cancer activity of Paris polyphylla var. yunnanensis - Li, Hai-Ling; Yan, Cui-Ping; Qi, Jun-Sheng; Zhang, Shuo; Guo, Dong-Qin; Gu, Wen-Chao; Wu, Ying-Mei; Wu, Yu; Zhou, Nong (Frontiers in Pharmacology, 2023)
Background:P. polyphylla var. yunnanensis, as a near-threatened and ethnic medicine in China, used to be a key ingredient in traditional Chinese medicine in treatment of traumatic injuries, sore throat, snakebites, and convulsions for thousands of years. However, there were no reports on the inverse relationship between the contents of heavy metals and saponins and its anti-breast cancer pharmacological activity in P. polyphylla var. yunnanensis. Methods: The present study aimed to reveal the characteristics of heavy metal contents and saponins and its anti-breast cancer pharmacological activity and their interrelationships in P. polyphylla var. yunnanensis from different production areas. The contents of heavy metal and steroidal saponins in P. polyphylla var. yunnanensis were analyzed by inductively coupled plasma mass spectrometry (ICP-MS) and the high-performance liquid chromatography technique, respectively. The Pearson correlation was used to study the correlation between saponins and heavy metals. 4T1 mouse mammary tumor cells were selected and cultivated for antitumor studies in vitro. Cell Counting Kit-8 (CCK-8) assay, Hoechst staining, and flow cytometry analysis were used for the examination of the proliferation and apoptosis of 4T1 tumor cells. Mouse breast cancer 4T1 cells were subcutaneously injected into BALB/c mice to construct a tumor model to explore the in vivo inhibitory effect on breast cancer. TUNEL assay and immunohistochemistry were used for the examination of the effect of P. polyphylla var. yunnanensis from different origins on cancer cell proliferation and apoptosis induction in 4T1 tumor mice. Results: Heavy metal contents were highly correlated with the content of steroidal saponins. The overall content of 10 metals in the three producing origins was of the order C3 >C2 >C1. The total content of eight steroidal saponins in the extracts of P. polyphylla var. yunnanensis from three different origins was C1 >C2 >C3. The Pearson correlation study showed that in all of the heavy metals, the contents of Cd and Ba were positively correlated with the main steroidal saponins in P. polyphylla var. yunnanensis, while Al, Cr, Cu, Fe, Zn, As, Hg, and Pb showed a negative correlation. In vitro experiments showed that the extracts of P. polyphylla var. yunnanensis from three origins could inhibit the proliferation and induce cell apoptosis of 4T1 cells in a concentration- and time-dependent manner, especially in the C1 origin. In vivo experiments showed that the extract of P. polyphylla var. yunnanensis from the three origins could inhibit the growth of tumors and induce the apoptosis of tumor cells. In the three origins, C1 origin had the lowest total heavy metal level but the highest total steroidal saponin level. Therefore, it showed a better effect in reducing the expression of the human epidermal growth factor receptor 2 (HER2) and Kiel 67 (Ki67) and increasing the expression of p53 in tumor tissues compared to the other origins. In conclusion, in the three origins, C1 origin exhibits antitumor pharmacological effects in vivo and in vitro which are better than those in the other origins. Conclusion: In this study, we found that with the increase of the heavy metal content, the content of steroid saponins and anti-breast cancer activity decreased. The results showed that the high content of the total heavy metals may not be conducive to the accumulation of steroidal saponins in P. polyphylla var. yunnanensis and lead to the low anti-breast cancer activity. The results of this study suggest that the content of heavy metals should be controlled in the artificial cultivation process of P. polyphylla var. yunnanensis.